2020
DOI: 10.1007/s00261-020-02783-1
|View full text |Cite
|
Sign up to set email alerts
|

Liver fat quantification: where do we stand?

Abstract: Excessive intracellular accumulation of triglycerides in the liver, or hepatic steatosis, is a highly prevalent condition affecting approximately one billion people worldwide. In the absence of secondary cause, the term nonalcoholic fatty liver disease (NAFLD) is used. Hepatic steatosis may progress into nonalcoholic steatohepatitis, the more aggressive form of NAFLD, associated with hepatic complications such as fibrosis, liver failure and hepatocellular carcinoma. Hepatic steatosis is associated with metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 100 publications
(212 reference statements)
0
29
0
5
Order By: Relevance
“…It is estimated that up to 30% of NAFLD patients may have NASH and have a greater risk of progression to end-stage liver disease [ 10 ]. Notably, NAFLD is the second most common etiology for liver transplantation and is projected to become the most common indication within the next decade [ 11 , 12 , 13 ]. Several studies have shown that increased liver fat content is also associated with non-liver-related mortality and morbidity.…”
Section: Why Is a Sensitive Methods For Liver Fat Assessment Important?mentioning
confidence: 99%
See 4 more Smart Citations
“…It is estimated that up to 30% of NAFLD patients may have NASH and have a greater risk of progression to end-stage liver disease [ 10 ]. Notably, NAFLD is the second most common etiology for liver transplantation and is projected to become the most common indication within the next decade [ 11 , 12 , 13 ]. Several studies have shown that increased liver fat content is also associated with non-liver-related mortality and morbidity.…”
Section: Why Is a Sensitive Methods For Liver Fat Assessment Important?mentioning
confidence: 99%
“…US is also not specific for liver fat. US estimates the liver fat content through the attenuation of soundwaves, which are also attenuated by many other liver diseases, such as fibrosis, hepatitis, and hemochromatosis [ 11 , 27 , 28 ]. The method is also potentially difficult to perform in individuals with high body mass index (BMI) and those at high risk for liver fat accumulation [ 29 , 30 ].…”
Section: Available Imaging Modalities For Liver Fat Assessment Compared To Mrsmentioning
confidence: 99%
See 3 more Smart Citations